2020
DOI: 10.1088/1361-6579/ab8e12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lung-to-finger circulation time in sleep study assessment: the Multi-Ethnic Study of Atherosclerosis

Abstract: Objectives: Lung-to-finger circulation time (LFCT) measured from sleep studies may reflect underlying cardiac dysfunction. We aimed to examine the distribution of LFCT in community-dwelling men and women in order to better understand the factors determining LFCT between and within subjects. Approach: We included participants of the Multi-Ethnic Study of Atherosclerosis (MESA) Sleep with polysomnography-based evidence of sleep apnea (defined by apnea hypopnea index >15 hr−1). In a randomly selected subset of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Importantly, previous studies have reported that LFCt and hypoxic burden can be used as significant predictors for cardiovascular disease and mortality [ 19 , 24 ]. Furthermore, we observed a trend of prolonged LFCt in obese and older patients, which is also consistent with previous findings [ 10 , 24 , 26 ]. It is known that obesity is directly associated with haemodynamic overload and a decrease in cardiac output occurs with age, which might explain the trend of prolonged LFCt in obese and older patients [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Importantly, previous studies have reported that LFCt and hypoxic burden can be used as significant predictors for cardiovascular disease and mortality [ 19 , 24 ]. Furthermore, we observed a trend of prolonged LFCt in obese and older patients, which is also consistent with previous findings [ 10 , 24 , 26 ]. It is known that obesity is directly associated with haemodynamic overload and a decrease in cardiac output occurs with age, which might explain the trend of prolonged LFCt in obese and older patients [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, severe hypoxaemia in patients with OSA has also been associated with increased heart rate, cardiac response and severe cardiovascular diseases [ 16 , 20 ]. Moreover, previous studies have demonstrated that LFCt has the potential to be used as a marker for cardiovascular health and comorbidities in sleep studies [ 8 , 24 , 26 ]. Therefore, although our study alone does not suffice to fully determining the clinical utility of LFCt with respect to cardiac impairment; the LFCt distribution reported in the present study showed that hypoxic severity can be significantly elevated even with short apnoeas, which has considerable implications for cardiac health prognosis in patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acsomega.3c05953. The Simulink file used in this work may be obtained from the corresponding author on reasonable request. The following additional works are referred to in the Supporting Information Model equations, parameters, and the method for simulating the spirometry test (PDF) …”
mentioning
confidence: 99%
“…The Simulink file used in this work may be obtained from the corresponding author on reasonable request. The following additional works are referred to in the Supporting Information …”
mentioning
confidence: 99%